Culturally contested pedagogy : battles of literacy and schooling between mainstream teachers and Asian immigrant parents - Li, Guofang, 1972- (SUNY series, power, social identity, and education., 2006)
"The voices of teachers, parents and students create a compelling ethnographic study that examines the debate between traditional and progressive pedagogies in literacy education and the mismatch of cross-cultural discourses between mainstream schools and Asian families. This book focuses on a Vancouver suburb where the Chinese population has surpassed the white community numerically and socioeconomically, but not politically, and where the author uncovers disturbing cultural conflicts, educational dissensions, and "silent" power struggles between school and home."--Jacket